Geological and Geochemical Prospecting for Gold Mineralization in Bode-Saadu Axis, Southwestern Nigeria - ADEBAYO, Samuel; OBASAJU, Daniel (GeoScience Engineering, 2021)
Geological and geochemical studies of gold mineralization in Bode-Saadu axis, Southwestern Basement Complex, Nigeria have been conducted in order to study their mode of occurrence, structural settings, pattern of distribution and potential. Geological studies reveal that granite and gneiss granite are the prominent rocks in the area and exist in the north-eastern, north-western and southwestern part of the area whereas mica and amphibole schist occur as low-lying exposure. Petrographic studies reveal spatial association between gold mineralization and the fractured zones. Geochemical studies show that the gold concentration in rocks and stream sediments from the region is low with the exception of a few areas with high values ​​and is related to the occurrence of fissure in the northeast-west direction. The distribution pattern of gold in the region is skewed NE-SW, indicating that gold mineralization is structurally controlled. Keywords: Geochemical prospecting; Geological studies; Gold mineralization; Structurally controlled.